Stimulus For Autism People Through Memorization Of The Al Qur’an At PD Salimah Gresik: Stimulus Penyandang Autis Melalui Hafalan Al Qur’an Di PD Salimah Gresik - Adrijanti; Bariroh, Siti; Anis, Fahimatul; Indahwati, Noor (Procedia of Social Sciences and Humanities, 2022)
People with autism have certain characteristics, each of child is different and has their own characteristics. However, in general situation, people with autism have characteristics like lack of focus, tantrums and hyperactivity, and less manageable. This condition makes the child unable to control his emotions, that sometimes it can cause uncontrollable behaviour like hurting himself and others around him, to control this condition a stimulus is needed, one of which is by reading the Qur'an. Reading the Qur'an can make you calm and control your emotions, but not all autistic children can read the Qur'an. Autistic children usually have a very strong memory, so they are able to memorize the holy verses of the Qur'an easily through methods that are suitable for the child's condition. From these characteristics, the method of memorizing the Qur'an that can be applied to people with autism also varies, but in general it is a method that only memorizes either by reading it repeatedly or with special assistance from parents or teachers. The methods of memorizing the Qur'an that can be applied to children with autism as a stimulus in controlling emotions include: the Sima'i Method, the Fahmul Mahfudz Method, the Isati'amul Mahfudz Method, the Talqin Method, the Wahdah Method.